Costa Rica : a journey through nature - Hepworth, Adrian, 1970- (Ithaca, New York : Comstock Publishing Associates, an imprint of Cornell University Press, 2024)
"Takes readers on a photographic journey through one of the most biologically diverse countries on the planet. This third edition replaces more than 45 percent of the book's images with new photographs taken during the author's recent explorations of Costa Rica. Approximately half of these introduce new species; the others provide new views of species included in the previous edition. A new introduction and conservation section inform the reader of the changing realities of Costa Rica's ecosystems"--
Guanacaste, life under the sun -- The Central Pacific, nature's oasis -- The Osa Peninsula, jungle -- The Central Divide, into the clouds -- The North Caribbean, living waters -- The South Caribbean, a secluded paradise -- Conservation and responsible tourism.
Includes index.
Keywords: Natural history -- Costa Rica -- Pictorial works; Natural history -- Costa Rica; Costa Rica -- Pictorial works